1974
DOI: 10.1055/s-0028-1093866
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of Monocomponent Porcine Insulin in Rabbits

Abstract: ceUular hypersensitivity in diabetes meUitus. Experimental induction of anti-pancreatic, cellular hypersensitivity and associated morphological B-cell changes in the rat. Acta allerg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Kerp et al 2<) have shown that injection of proinsulin in rabbits does not lead to the formation of insulin antibodies but rather to low-titer proinsulinspecific antibodies. Kumar et al 21 have demonstrated that MC insulin is antigenic in rabbits. Schlichtkrull's experiments have been criticized in that some studies were carried out with the regular form of MC insulin in neutral solution.…”
Section: Discussionmentioning
confidence: 98%
“…Kerp et al 2<) have shown that injection of proinsulin in rabbits does not lead to the formation of insulin antibodies but rather to low-titer proinsulinspecific antibodies. Kumar et al 21 have demonstrated that MC insulin is antigenic in rabbits. Schlichtkrull's experiments have been criticized in that some studies were carried out with the regular form of MC insulin in neutral solution.…”
Section: Discussionmentioning
confidence: 98%
“…Kumar and Miller (1973) showed that a number of patients treated with commercial insulins did not develop proinsulin-specific antibodies, although they all formed insulin antibodies. The same authors were unsuccessful in demonstrating proinsulin-specific antibodies in commercial-insulin-treated rabbits (Kumar, Mehtalia and Miller 1974).…”
Section: Discussionmentioning
confidence: 99%